An in situ and morphometric study of maize (Zea mays L.) cob rondel phytoliths from Southwestern North American landraces. (February 2021) - Yost, Chad L.; Michas, McCaela; Adams, Karen R.; Swarts, Kelly; Puseman, Kathryn; Ball, Terry
Highlights: Computer-assisted morphometric analysis was applied to maize cob rondel phytoliths. Maize glumes produce phytoliths (rondel s), whereas lemmas and paleas do not. Maize cupules are devoid of rondel s, except presumably at glume attachment points. Maize cob location affects rondel size but not shape morphometries. Our rondel morphometries cannot discriminate between 24 indigenous maize landraces. Abstract: We present the first comprehensive computer-assisted morphometric analysis of microscopic rondel 1 phytoliths (plant opal microfossils) produced in the cobs of 24 historic Southwestern North American landraces of maize ( Zea mays L.) after all were grown in a well-documented agronomic field study. We also present an in situ study of the location of rondel phytolith production within the maize cob and provide a detailed review of previous maize phytolith studies. We found that glumes contained abundant rondel phytoliths throughout the tissue; however, lemma/palea tissue contained no phytoliths. In contrast, cupule tissue had some areas with abundant phytoliths, some with fewer scattered phytoliths, and vast areas that contained no rondel phytoliths. The rondel -rich areas appear to be where the glumes had once attached to the cupule and may be remnants of glume tissue adhering to the cupule. From the morphometric study, we found there were significant differences in the size morphometries of glume rondel s depending on their cob location (top, middle, base) but no significant differences in shape morphometries. Using shape morphometries, we could not discriminate reliably among maize cob rondel phytoliths produced by the diverse landraces considered. The inclusion of morphometrics from areas in addition to or in combination with the outer periclinal surface may allow for some discrimination of maize landraces and is an avenue that should be explored further. Although our approach was not successful at identifying differences between essentially modern landraces, there may be significant rondel phytolith morphometric differences between wild, progenitor, and domesticated Zea .